Efect of Ethanolic Leaf Extract of Sauraunia vulcani Korth on Lymphocyte and IL-In Immunized Rats - Erlintan Sinaga; Syafruddin Ilyas; Panal Sitorus (International Journal of Science, Technology & Management, 2020)
Ethanolic leaf extract of Saurauia vulcani Korthor pirdot in Indonesia was evaluated to improve the number of erythrocytes in laboratory rats after being immunized with sheep red blood cells (SRBC). This study was conducted in an experimental manner using a non-factorial Completely Randomized Design (CRD) with four treatments and six replications. The tested animals were 24 rats (Rattus norvegicus) maintained in the laboratory. The experimental designs were designated as follows: G0as a control group treatedwith regular animal feed,G1 was treatedwith 0.1 mLSRBC, G2was treated with 500 mg ethanolic leaf extract of Saurauia (EES)/kg body weight (BW), G3 was treated with 500 EES/kg BW and 0.1 mL SRBC. The immunological effect was monitored by analyzing the level of interleukin-2 (IL-2) using ELISA, lymphocytes using ABX Microx 60, and liver histopathology. The results showed that lymphocyte levels was increased in G2 and G3 but not significant to G0. The IL-2 level in G1 was recorded the highest among groups due to the treatment using SRBC. The percentage of necrotic cells in G1was 5.8%, followed by G3 with 2.3%. The morphologies of liver histology were normal, parenchymatous and hydropic degenerations, and necrosis. The phytochemical constituents in ethanolic leaf extract of S. vulcanipossessed an immunological effect through the increased lymphocytes, reduction of IL-2, and protection through normal liver histopathology in rats.